NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA: PENGARUH RASIO KEUANGAN DAN STRUKTUR KEPEMILIKAN - Vania, Belinda; Lekok, Widyawati (E-Jurnal Akuntansi TSM, 2025)
The purpose of this research is to provide empirical evidencen regarding the effect of profitability, firm size, investment decision, financing decision, dividend policy, managerial ownership, and cash holding on firm value. The sample in this study consists of 45 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2021 to 2023, with a total of 135 data. The sampling method used is purposive sampling, and the data are analyzed using multiple regression analysis. The research findings indicate that profitability, financing decision, dan dividend policy have an impact on firm value. All three variables have a positive impact on firm value. Higher profitability indicates that the company can maximize its profit through good performance, which sends a positive signal to investors to invest, thus contributing to a higher firm value. A higher financing decision value reflects the company’s ability to manage debt to support its growth and achieve future targets, which in turn attracts investors and leads to increase in firm value. Moreover, a higher dividend policy serves as indicator of the company’s financial stability, which attracts investors and contributes to an increase in firm value. Meanwhile, other independent variables, namely firm size, investment decision, managerial ownership, and cash holding, do not have an impact on firm value.